Design and evaluation of a blended mental health curriculum for undergraduate medical education in Pakistan - Aisha Sanober Chachar; Sana Asif Siddiqui; Humera Saeed; Azra Naseem; Ayesha I Mian (University of Johannesburg, 2020)
There is a significant shortage of qualified psychiatrists and related service providers in Pakistan; this occurs in the backdrop of burgeoning evidence of a high prevalence of mental health disorders in the country. At the Aga Khan University Medical College, Psychiatry has been taught to the undergraduates as a mandatory one-month clinical rotation since 1987. AKU is the only medical college with a formal psychiatry training at the undergraduate level. In 2017, a team of faculty members reassessed the curriculum, teaching methodology and learning outcomes of the psychiatry rotation. As a result, an outcome-based, blended curriculum was devised that integrated virtual and classroom-based learning with patient skills training. The new curriculum has now been in implementation for one year. At the end of the rotation, a questionnaire was administered to determine students' experience of online learning. WEBLEI was adapted to measure students' perceptions across four subscales. Data was gathered from learners' use of the virtual learning system, participation in facilitator-based sessions and the clinical teaching and learning. Students were also asked to compare didactic face-to-face sessions with blended learning. Blended learning scored higher on all measures such as student engagement, critical thinking, student-led learning and alignment of assessment method with learning outcomes. The analysis of this data has informed future directions regarding the design and implementation of a Pakistan-wide mental health program. This study also highlights the challenges of curriculum design and its implications in the broader context of Pakistan. The results add to the existing literature about the experience, challenges and successful outcomes of designing a blended curriculum for Pakistan. Keywords: Blended learning, Integrated curriculum, Mental health, Learning analytics, Pakistan How to cite this article: Chachar, A.S., Siddiqui, S.A., Saeed, H., Naseem, A. & Mian, A.I. 2020. Design and evaluation of a blended mental health curriculum for undergraduate medical education in Pakistan. Scholarship of Teaching and Learning in the South. 4(2): 100-117. https://doi.org/10.36615/sotls.v4i2.111. This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/